2007
DOI: 10.1063/1.2436850
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative experiments with electrons in a positively charged beam

Abstract: Intense ion beams are an extreme example of, and difficult to maintain as, a non-neutral plasma. Experiments and simulations are used to study the complex interactions between beam ions and (unwanted) electrons. Such "electron clouds" limit the performance of many accelerators. To characterize electron clouds, a number of parameters are measured including: total and local electron production and loss for each of three major sources, beam potential versus time, electron line-charge density, and gas pressure wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
(29 reference statements)
1
6
0
Order By: Relevance
“…We have only a short experiment in which to measure electron cloud effects, so it is essential to benchmark simulations with these results, so as to validate the simulations that can then examine the effects in longer accelerators. We have shown that, with sufficient electron density, significant effects can be observed and accurately simulated with only four quadrupole magnets [6].…”
Section: Issuementioning
confidence: 94%
See 2 more Smart Citations
“…We have only a short experiment in which to measure electron cloud effects, so it is essential to benchmark simulations with these results, so as to validate the simulations that can then examine the effects in longer accelerators. We have shown that, with sufficient electron density, significant effects can be observed and accurately simulated with only four quadrupole magnets [6].…”
Section: Issuementioning
confidence: 94%
“…Observed and simulated an oscillation involving bunching of electrons in a quadrupole magnet. Obtained good agreement on the frequency, wavelength, and amplitude of the oscillations [6]. 6.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Experiments were performed to study the matching and transport of a space-charge dominated ion beam in the solenoid transport channel shown in Figure 1, including the effects of gas and electrons on the beam. These experiments provide a basis for comparison of solenoid transport with magnetic quadrupole transport in accelerators, for application to warm-dense matter and heavy-ion fusion [10]. The beam energy and current was the same as indicated in Section 2.…”
Section: Progress In E-cloud Researchmentioning
confidence: 99%
“…Copious electrons are generated by slamming the beam onto the end plate. We study electron effects in the magnetic section, which is heavily instrumented with diagnostic devices and suppressor electrodes dedicated to the various measurements of electron flux, electron energy spectrum, and gas analysis [26][27][28][29][30][31][32]. The primary electrons created at the end plate propagate upstream, entering only two quadrants of the fourth (last) magnet because of the sign of E × B.…”
Section: The High Current Experimentsmentioning
confidence: 99%